Flow cytometry-based characterization of underlying clonal B and plasma cells in patients with light chain amyloidosis - Kriegsmann, Katharina; Schönland, Stefan; Jauch, Anna; Andrulis, Mindaugas; Ho, Anthony Dick; Goldschmidt, Hartmut; Hegenbart, Ute; Hundemer, Michael (Cancer medicine, 2016)
Systemic amyloid light chain (AL) amyloidosis is a life-threatening protein deposition disorder; however, effective therapy can dramatically improve the prognosis of AL patients. Therefore, accurate diagnosis of the underlying hematologic disease is important. Multi-parameter flow cytometry (MFC) is a reliable method to analyze lymphatic neoplasias and to detect even a small lymphatic clone. We analyzed the presence of clonal plasma cell (PC) and B cells in the bone marrow of 63 patients with newly diagnosed AL amyloidosis by MFC. We compared the results with the levels of monoclonal protein, the histopathology and cytogenetic results. As reference of light chain restriction, we used the immunohistochemical results of κ or λ positive amyloid deposits in various tissues. MFC identified underlying clonal lymphatic cells in all but two patients (61 of 63, 97%). Sixty-one patients harbored malignant PCs, whereas B-cell lymphomas were identified in two patients. Furthermore, MFC indicated at least one putative immunotherapeutical target (CD20, CD38, CD52, or SLAMF7) on malignant PCs in all but one patient. These results demonstrate that MFC is a reliable tool for an accurate diagnosis of the underlying hematologic disease and the detection of potential immunotherapeutical targets in patients with AL amyloidosis.